1969
DOI: 10.1016/0014-4800(69)90049-5
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocephalus as a sequela of experimental myxovirus infections

Abstract: An immunological and histoimmunological study of gastric sulphoglycoproteins in healthy and aspirin-treated dogs I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
1

Year Published

1974
1974
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(33 citation statements)
references
References 20 publications
3
29
1
Order By: Relevance
“…Certainly, a better understanding of the precise mechanism(s) by which mumps virus leads to hydrocephalus will ultimately be required for a better appreciation of the role of virus-infected subventricular neurons in hydrocephalus development. To date, the preponderance of data suggests that hydrocephalus is the result of accumulation of virus-infected cell debris in the aqueduct of Sylvius, blocking cerebrospinal fluid egress (27,28,49). A similar mechanism is believed to be responsible for mumps virus hydrocephalus in humans (21,41,55).…”
Section: Discussionmentioning
confidence: 99%
“…Certainly, a better understanding of the precise mechanism(s) by which mumps virus leads to hydrocephalus will ultimately be required for a better appreciation of the role of virus-infected subventricular neurons in hydrocephalus development. To date, the preponderance of data suggests that hydrocephalus is the result of accumulation of virus-infected cell debris in the aqueduct of Sylvius, blocking cerebrospinal fluid egress (27,28,49). A similar mechanism is believed to be responsible for mumps virus hydrocephalus in humans (21,41,55).…”
Section: Discussionmentioning
confidence: 99%
“…The lesions in one of the fetuses taken at 28 days were similar to those seen in the principal fetuses taken at 7 days. In the other control fetus from the same gilt, the lung was of normal size but had 5 Lung from principal fetus taken 7 days after virus inoculation. Severe epithelial destruction has resulted in obliteration of bronchial buds (short arrows).…”
Section: Resultsmentioning
confidence: 98%
“…Studies with common respiratory pathogens of myxoviruses and paramyxoviruses have revealed that they cause acute inflammation of the ependyma and meninges with various degrees of parenchymal involvement when viruses are inoculated into the brain of suckling rodents (5,13,19) . Hydrocephalus has developed in some suckling rodents as a sequela of intracerebral inoculation of such viruses (5,13,19) .…”
Section: Discussionmentioning
confidence: 99%
“…Hydrocephalus has developed in some suckling rodents as a sequela of intracerebral inoculation of such viruses (5,13,19) . Besides hydrocephalus as a late effect of infection of these viruses in the brain of suckling rodents, virus antigens were reported to persist in the brain of suckling mice inoculated intracerebrally with Sendai virus, one of the paramyxoviruses, for as long as 4 months (19) .…”
Section: Discussionmentioning
confidence: 99%